Who is policing the Police and Crime Commissioners?. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to explore how the Police and Crime Commissioners have been scrutinised in their first nine months in office, focusing primarily on one particular force area.Design/methodology/approach – A brief analysis of the most current writing on this topic, including official documents such as minutes of police and crime panel meetings and Home Affairs Committee and Welsh Affairs Committee evidence sessions, as well various online news sources are provided. Academic literature spanning 30 years is also drawn upon.Findings – In considering particular major events in the first nine months of the implementation of Police and Crime Commissioners, central government have been required to take a more prominent role in scrutiny in certain regions than first envisaged, due to ambiguity of legislative guidelines.Research limitations/implications – As an exploratory paper, one force area (Gwent) is the primary focus, sampled because of the issues faced in that area and its widespread coverage in the media.Practical implications – Problems with the legislative guidance for Police and Crime Commissioners, Police and Crime Panels and other involved agencies and individuals are highlighted.Originality/value – The paper contributes to the body of research investigating how the new policing governance framework in England and Wales is unfolding in practice. It is informed by both academic perspectives and real life examples.